Apollo : the International Magazine of the Arts (titel varieert: Apollo : the International Art Magazine; originele titel: Apollo : A Journal of the Arts (1925)). (Londen : The Apollo Press, 1925)
Apollo is an English-language monthly magazine covering the visual arts of all periods from antiquity to the present day.pollo was founded in 1925, in London. The contemporary Apollo features a mixture of reviews, art-world news and scholarly articles.[2] It has been described as "The International Magazine for Collectors". Apollo is owned by the Barclay brothers through the Press Holdings Media Group company.The magazine rewards excellence in arts through annual Apollo Magazine Awards. (Wikipedia)
Https://en.wikipedia.org/wiki/Apollo_(magazine)
Https://www.apollo-magazine.com/ (login)
Engels
Tijdschriften